2019
DOI: 10.1371/journal.pone.0220530
|View full text |Cite
|
Sign up to set email alerts
|

TET1 regulates fibroblast growth factor 8 transcription in gonadotropin releasing hormone neurons

Abstract: Fibroblast growth factor 8 (FGF8) is a potent morphogen that regulates the ontogenesis of gonadotropin-releasing hormone (GnRH) neurons, which control the hypothalamus-pituitary-gonadal (HPG) axis, and therefore reproductive success. Indeed, FGF8 and FGFR1 deficiency severely compromises vertebrate reproduction in mice and humans and is associated with Kallmann Syndrome (KS), a congenital disease characterized by hypogonadotropic hypogonadism associated with anosmia. Our laboratory demonstrated that FGF8 signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
8
0
1
Order By: Relevance
“…All known forms of inheritance have been described: autosomal dominant, recessive and with variable penetrance; X-linked recessive; oligogenicity, and transmission linked to an imprinting locus. Moreover, as already reported for Fgf8 signaling system ( 42 , 43 ), also interferences in the pre-hypothalamic epigenome (throught DNMTs/TETs proteins) could have major consequences on GnRH system neurodevelopment, resulting in CHH disorder. Due to the variable expressivity and incomplete penetrance of the genetic defects, together with the actual or potential impact of oligogenicity and epigenome modifications, there is a broad spectrum of phenotypes, whether with non-reproductive defects or pure neuroendocrine phenotype, and ranging from complete CHH, with LH/GnRH apulsatility and absent pubertal development (around 2/3 of cases), to partial hypogonadism with residual LH/GnRH pulsatility (low amplitude, low frequency, or nocturnal-only pattern) resulting in arrested early puberty (around 1/3 of cases), and even reversible CHH in 5 to 20% of cases patients ( 44 ).…”
Section: Genetics Of Chhmentioning
confidence: 68%
“…All known forms of inheritance have been described: autosomal dominant, recessive and with variable penetrance; X-linked recessive; oligogenicity, and transmission linked to an imprinting locus. Moreover, as already reported for Fgf8 signaling system ( 42 , 43 ), also interferences in the pre-hypothalamic epigenome (throught DNMTs/TETs proteins) could have major consequences on GnRH system neurodevelopment, resulting in CHH disorder. Due to the variable expressivity and incomplete penetrance of the genetic defects, together with the actual or potential impact of oligogenicity and epigenome modifications, there is a broad spectrum of phenotypes, whether with non-reproductive defects or pure neuroendocrine phenotype, and ranging from complete CHH, with LH/GnRH apulsatility and absent pubertal development (around 2/3 of cases), to partial hypogonadism with residual LH/GnRH pulsatility (low amplitude, low frequency, or nocturnal-only pattern) resulting in arrested early puberty (around 1/3 of cases), and even reversible CHH in 5 to 20% of cases patients ( 44 ).…”
Section: Genetics Of Chhmentioning
confidence: 68%
“…These two factors are considered markers of cartilage production, which promote chondrocyte differentiation and produce type II collagen fibres necessary for the formation of chondrocyte extracellular matrix 10,52,55,56 . FGF‐8 binds to FGFR3 and FGFR1, which play a role in early chondrocyte proliferation, and activates the MAPK, MEK‐ERK, JNK and PI3K/Akt pathways and corresponding downstream molecules such as BMP‐7, GP130, MSX‐1 and VGEF, to induce the proliferation of immature chondrocytes and facilitate a repair on cartilage 49,57–59 . Activation of these molecules increases the migration of chondrocytes and promotes the secretion of aggrecan and chondroitin sulphate, which increase the proliferation of chondrocytes and form positive feedback 13,28,57,60–62 .…”
Section: Overview Of Fgf‐8 In Normal Cartilagementioning
confidence: 99%
“…The tight interplay between genes and environment in FHA development and the identification of a few genetic variants associated to FHA predisposition, suggest that epigenetic factors may represent additional candidates underlying FHA pathogenesis. Recent studies on mice have reported a pivotal role of epigenetics in controlling GnRH neuron ontogenesis, through the coordinated actions of Dnmt3b, Tet1 and Ezh2 on the Fgf8 transcription (49). Moreover, in vitro studies further highlighted that the GnRH gene responds to external stimuli by modulating chromatin modifications also in mature GnRH neurons (50).…”
Section: The Epigenetic Contribution To Fhamentioning
confidence: 99%